Inadequate Bioavailability of Intramuscular Epinephrine in a Neonatal Asphyxia Model - Sara K. Berkelhamer; Payam Vali; Jayasree Nair; Sylvia Gugino; Justin Helman; Carmon Koenigsknecht; Lori Nielsen; Satyan Lakshminrusimha (Frontiers Media S.A., 2022)
BackgroundOver half a million newborn deaths are attributed to intrapartum related events annually, the majority of which occur in low resource settings. While progress has been made in reducing the burden of asphyxia, novel approaches may need to be considered to further decrease rates of newborn mortality. Administration of intravenous, intraosseous or endotracheal epinephrine is recommended by the Newborn Resuscitation Program (NRP) with sustained bradycardia at birth. However, delivery by these routes requires both advanced skills and specialized equipment. Intramuscular (IM) epinephrine may represent a simple, low cost and highly accessible alternative for consideration in the care of infants compromised at birth. At present, the bioavailability of IM epinephrine in asphyxia remains unclear.MethodsFour term fetal lambs were delivered by cesarean section and asphyxiated by umbilical cord occlusion with resuscitation after 5 min of asystole. IM epinephrine (0.1 mg/kg) was administered intradeltoid after 1 min of positive pressure ventilation with 30 s of chest compressions. Serial blood samples were obtained for determination of plasma epinephrine concentrations by ELISA.ResultsEpinephrine concentrations failed to increase following administration via IM injection. Delayed absorption was observed after return of spontaneous circulation (ROSC) in half of the studies.ConclusionsInadequate absorption of epinephrine occurs with IM administration during asphyxial cardiac arrest, implying this route would be ineffective in infants who are severely compromised at birth. Late absorption following ROSC raises concerns for risks of side effects. However, the bioavailability and efficacy of intramuscular epinephrine in less profound asphyxia may warrant further evaluation.